Length-weight relationship and gonadal index of juvenile bluestripe snapper Lutjanus kasmira (Forsskål, 1775) in the waters around Tanamon Village South Minahasa - Malurung, Yulianti -; Bataragoa, Nego E.; Salaki, Meiske S.; Pratasik, Silvester B.; Moningkey, Ruddy D. (Jurnal Ilmiah Platax, 2021)
This study aims to determine the length-weight relationship, growth patterns, and gonadal index of juvenile bluestripe snapper Lutjanus kasmira. Samples were collected using a hand line with a hook numbered  3 and a monofilament fishing line numbered 80. Sampling activities were carried out on July 26th – August 4th, August 26th - September 4th, and October 10th, 2020. A total of 70 fish, 22 females and 48 males was caught. Female length distribution ranged from 104 to 150 mm with a weight range of 18.19-55.87 g, while male length ranged from 107 to 150 mm in length with a weight of 19.00-57.00 g. The length-weight relationship was indicated with W= 0.0177L2.9344 (R2=0,7816) for males and W = 0.012L3.0817 (R2=0,8976) for females with isometric growth pattern. The length-weight relationship for combined sexes was W= 0.0156L2.9816 (R2=0,8186) with an isometric growth pattern. The gonadal maturity for all samples was at immature and developing stages. The gonadal index in female snapper at immature was 0.16 and developing was 0.41, whereas the male gonadal maturity index at immature was 0.14 and developing was 0.38.Keywords: Lutjanus kasmira; length-weight; gonad maturity; gonadal indexAbstrakPenelitian ini bertujuan untuk mengetahui hubungan panjang berat, pola pertumbuhan dan indeks  gonad  ikan kakap Lutjanus kasmira. Sampel ikan ditangkap menggunakan pancing ulur mata pancing nomor  3 dan tali monofilament nomor 80. Aktivitas pengambilan sampel dilakukan masing-masing pada 26 Juli-4 Agustus, 26 Agustus-4 September 2020, dan 10 Oktober 2020. Sebanyak 70 individu sampel diperoleh, 22 betina dan 48 jantan. Sebaran ukuran panjang ikan betina  104-150 mm dan berat 18,19-55,87 g. Sebaran ukuran panjang ikan jantan 107-150 mm dan berat 19,00-57,00 g.     Hubungan panjang-berat diperoleh W= 0,0177L2,9344 (R2=0,7816) untuk jantan dan W = 0,012L3,0817 (R2=0,8976) untuk betina dengan pola pertumbuhan isometrik. Gabungan ikan kakap jantan dan betina diperoleh W= 0,0156L2,9816 (R2=0,8186)  dengan pola pertumbuhan isometrik. Tingkat kematangan gonad  (TKG) terhadap seluruh sampel baik jantan maupun betina berada pada TKG I (belum matang) dan TKG II (berkembang). Indeks  gonad pada ikan kakap betina pada TKG I sebesar 0,16 dan TKG II sebesar 0,41. Indeks kematangan gonad ikan kakap jantan pada TKG I sebesar 0,14 dan TKG II sebesar 0,38.Kata Kunci: Lutjanus kasmira, panjang-berat, kematangan gonad, indeks gonad